Ultrasound-Guided Posterior Tibial Nerve Block for Plantar Foot Foreign Body Removal. Issue 5 (May 2020) - Moake, Matthew M.; Presley, Bradley C.; Barnes, Ryan M.
Abstract : Abstract: Ultrasound-guided regional anesthesia is a growing modality within the pediatric emergency department. Here we present a case where a posterior tibial nerve block was used for anesthesia during foreign body removal from the plantar foot. We further review the technique and literature regarding this straightforward and highly effective procedure.